Total synthesis of umuravumbolide and hyptolide through silicon-tethered ring-closing metathesis - Chowdhury, Partha Sarathi; Kumar, Pradeep (European Journal of Organic Chemistry, 2013)
The total synthesis of umuravumbolide and hyptolide has been achieved in a efficient manner by using temporary silicon-tethered ring-closing metathesis and cross-coupling reactions as key steps. The stereogenic centres were generated by means of proline-catalysed -aminoxylation of aldehydes and Brown's asymmetric allylation method.
Keywords: lactones; Metathesis; Silanes; synthetic methods; Total synthesis; Wittig reactions

Stereoselective approach to 2,6-disubstituted piperidin-3-ol: synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline - Jha, Vishwajeet; Kauloorkar, Shruti Vandana; Kumar, Pradeep (European Journal of Organic Chemistry, 2014)
A simple and highly efficient approach to an enantioenriched 2,6-disubstituted piperidin-3-ol skeleton is developed from an aldehyde as a starting material by using organocatalytic and asymmetric dihydroxylation as the key steps. Its application to the total synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline is also reported.
Keywords: alkaloids; Amination; Amino alcohols; synthetic methods; Wittig reactions